2022
DOI: 10.1002/suco.202200503
|View full text |Cite
|
Sign up to set email alerts
|

Study on the flexural properties and fiber‐selection method of fiber‐reinforced geopolymer concrete

Abstract: In order to study the effect of different types of fibers on the bending properties of geopolymer concrete (GPC), a series of fiber‐reinforced geopolymer concrete (FRGPC) samples were prepared, and their flexural properties were evaluated by four point bending test and bending toughness evaluation index. Then, based on the fiber characteristic value (λ), a new bending strength prediction model and a three‐dimensional (3D) curved surface prediction model of the bending toughness of FRGPC are proposed and fitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The shrinkage testing and theoretical research are more complex than investigating the mechanical properties of metakaolin-based geopolymers. Numerous studies have found that the mixture ratio (alkali activator content [17,18], slag content [18], fly ash content [19], and water-binder ratio [20]), curing method [17,21], and additives) significantly influences the volume stability of metakaolin-based geopolymers [22]. Fu et al [23] reported that metakaolin can coarsen the pore structure of hardened slag, thereby reducing autogenous and drying shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…The shrinkage testing and theoretical research are more complex than investigating the mechanical properties of metakaolin-based geopolymers. Numerous studies have found that the mixture ratio (alkali activator content [17,18], slag content [18], fly ash content [19], and water-binder ratio [20]), curing method [17,21], and additives) significantly influences the volume stability of metakaolin-based geopolymers [22]. Fu et al [23] reported that metakaolin can coarsen the pore structure of hardened slag, thereby reducing autogenous and drying shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing urbanization, industrialization, and construction needs required by infrastructure projects gradually increase the demand and production of Portland cement (PC) every year. 1 Portland cement, which is the most common binder material used to meet the increasing need for concrete in the world, causes great energy consumption and high CO 2 emissions due to its production method. Each year, approximately 4 billion tons of CO 2 is released into the atmosphere during PC production, and this release corresponds to 5%-7% of total greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for concrete is increasing all over the world, and it is expected that this demand will continue in the future. Also, concrete is the second most important material in the word after the water 1,2 . The ordinary Portland cement (OPC) is a binder material of conventional concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Also, concrete is the second most important material in the word after the water. 1,2 The ordinary Portland cement (OPC) is a binder material of conventional concrete. However, the production phase of OPC is a harmful process for global warning.…”
Section: Introductionmentioning
confidence: 99%